Muş İl’inde Yerleşme Tiplerinin Coğrafi Dağılışı - Durmuş, Esen; Dölek, İskender (My University, 2019)
Yerleşmeler genel olarak nu?fuslarına, kuruluş yerlerine, dokularına ve hâkim ekonomik fonksiyonlarına göre sınıflandırılmıştır. Muş ilinde yerleşme tiplerinin coğrafi dağılışının belirlenmesinin amaçlandığı bu çalışmada, aynı zamanda yerleşmelerin kuruluş yeri seçimi, konumu, yu?kselti basamakları ve yu?ru?tu?len ekonomik faaliyetlere göre dağılışı u?zerinde etkin olan coğrafi unsurlar da belirlenmiştir. Araştırmada, yerleşme tiplerinin Muş ilindeki dağılışına farklı bir açıdan bakılarak yu?kselti faktöru? ön planda tutulmuştur. Her bir yu?kselti basamağında yer alan yerleşme sayısı ve yerleşme tipi, yu?kselti basamağının doğal koşulları göz önu?nde bulundurularak analiz edilmiştir. Fiziki koşulların insan yaşamına ve faaliyetlerine sağladığı olanakların arttığı kesimlerde hem yerleşme sayısında hem de nu?fusta belirgin artışlar gözlenmiştir. Muş ilinde farklı jeomorfolojik birimlerin bulunduğu alanlarda kurulmuş olan yerleşmelerin, yu?kseltiye bağlı olarak sayı ve tiplerinin yanında şekil ve dokuları da değişmektedir. Farklı morfolojik u?nitelerde kurulan yerleşmelerde ekonomik fonksiyonun tu?ru? ve nu?fusun dağılışı da değişmektedir. 1/25.000 ölçekli 87 adet topografya haritası taranarak yerleşme tipleri işaretlenmiş, sayısal ortamda 250 m aralıklarla beş yu?kselti basamağı belirlenmiş, dağ, ova, plato gibi ana yer şekilleri ayırt edilmiş ve yerleşme tipleri ile olan ilişkileri belirlenmiştir. Muş ilinde 2 şehir (Muş ve Bulanık), 21 kasaba (Hasköy, Korkut, Malazgirt ve Varto ilçe merkezleri ile 17 belde) 367 köy, 279 mezra, 96 yayla, 23 kom ve 5 ağıl yerleşmesi beş farklı yu?kselti basamağında bulunmaktadır. Muş’ta yerleşmelerin ve kırsal nu?fusun en yoğunluk gösterdiği yu?kselti basamağı 1551-1800 m’ler arasındaki basamaktır.

The settlements were generally classified according to their population, location, texture and dominant economic functions. In this study, which aimed to identify the geographical distribution of settlement types in the province of Muş, the geographic elements which were effective on the distribution of settlement location preferences, position, elevation steps of settlements and economic activities carried out were also identified. In the study, the elevation factor was prioritized by looking at the distribution of settlement types in the province Muş from a different perspective. The number of settlements and the settlement type in each elevation step were analyzed taking into account the natural conditions of the elevation step. There were, it was observed, some notable increases in both the number of settlements and population in the regions where the opportunities provided by the physical conditions for human life and activities increased. Shape and texture of the settlements established in the areas where different geomorphological units are present in the province of Muş, also vary in terms of number and type based on the elevation. In the settlements established in different morphological units, the type of economic function and population distribution also differ. The settlement types were marked by scanning a total of 87 topography maps with 1 / 25,000 scale and five elevation steps were identified at 250 m intervals in digital environment, main landforms such as mountain, plain and plateau were distinguished and their relations with settlement types were identified. In the province of Muş two cities (Muş and Bulanık), 21 districts (Hasköy, Korkut, Malazgirt and Varto district centers and 17 small towns) 367 villages, 279 hamlets, 96 highlands, 23 mountain houses and 5 hovel settlements are located in five different elevation step. The elevation step in the province of Muş where the settlements and rural population are the densest is between 1551 and 1800 meters.
GEOGRAPHICAL DISTRIBUTION OF THE SETTLEMENT TYPES IN THE PROVINCE OF MUŞ
Keywords: Coğrafya